Endogenous Candida Endophthalmitis as a Rare Complication of Trans-Urethral Lithotripsy in a Healthy Woman: A Case Report - Mohammad Shirvani; Shahla Hosseini; Mehrnoosh Maalhagh; Sahar Mohaghegh (Türk Oftalmoloji Dergisi, 2019)

(untitled)
Endogenous endophthalmitis is a serious sight-threatening ocular emergency that usually occurs in patients with serious underlying risk factors. In this report, we describe a case of endogenous Candida endophthalmitis following trans-urethral lithotripsy in an immunocompetent woman. In our case, the retinal lesion regressed completely and vision was restored. We discuss diagnostic procedures and management strategies in this article.